The Influence of Culture on Marketing Communications. Case of Japan - Miesiączek, Magdalena (Wpływ kultury na komunikację marketingową na przykładzie Japonii, 2022)
The subject of the article is culture, its elements and identifying the impact of culture on marketing communication strategies. In addition, the aim is to obtain information on the characteristics and elements of culture specific to Japan, and to examine the impact of Japanese culture on marketing communications. Culture, which is a very broad topic, includes people’s lifestyles, ways of behavior, attitudes, beliefs, values and norms, systems of thinking and learning, and traditions transmitted from generation to generation. Elements of culture influence marketing communications and the marketing strategy which is used by salespeople to effectively increase sales. For communication to be effective, the message and the way it is conveyed must be tailored to the culture of the recipient. The article begins with brief overview and the explanation of the role of marketing communications. It includes the description of all the marketing communications mix factors: advertising, sales promotion, personal selling, public relations and direct marketing. It allows for looking deeper into layers of culture such as: symbols, heroes, rituals and values with brief explanation of each of them. It also includes description of Hofstede’s cultural dimensions and high-low context cultures proposed by Hall. These dimensions were used to analyze Japanese society, the characteristics of Japanese culture and its impact on marketing communications.
[w:] Ekonomia i międzynarodowe stosunki gospodarcze / pod red. Aleksandry Kuźmińskiej-Haberli. - Wrocław: Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2022, s. 74-88
Keywords: marketing communications; culture; Japan; Japanese culture; marketing communications mix; komunikacja marketingowa; kultura; Japonia; kultura japońska; miks komunikacyjny